Study into mycelium coating on 3D printed scaffolds - Peh, Randon Jia Hao (Nanyang Technological University, 2023)
Mycelium composites have shown to have great potential for future applications such as a building material. These composites are great as an alternative biodegradable material. However, conventional materials are still preferred due to its mechanical properties. Hence, this project aims to improve mycelium composite by utilising a scaffold. Using a novel agar-coating method to fabricate mycelium composites, this project aims to improve mechanical properties and also to provide better mycelium growth even into hard to reach areas. This project compares the traditional method of growing mycelium with substrate with the agar-coating method. Experiments were also conducted to control the mycelium growth direction. The result of the project shows a possibility for utilizing mycelium for future application.